Associations of family characteristics with perceptions of care among parents of children with autism. (16th October 2015) - Sobotka, S. A.; Francis, A.; Vander Ploeg Booth, K.
Abstract: Background: Although autism spectrum disorder (ASD) is an increasingly common chronic disability, primary care provider (PCPs) report deficits in providing primary care for children with ASD, and parents report lapses in receipt of medical home services. In this study, we describe parental experiences with specific medical home components for their children with ASD. Methods: We analysed data from all children within the National Survey of Children with Special Health Care Needs database with ASD and a usual place for care ( n  = 2859). We evaluated the receipt of core medical home components: accessible, comprehensive, coordinated, family centred and compassionate and culturally sensitive care. Results: Children were mean age 10.1 years, and respondents were 75% mothers and 95% reported having a primary care provider (PCP). Seventy‐one percent reported care to be usually comprehensive, over three‐fourths of respondents reported care to be family centred and compassionate and 87% reported care to be culturally sensitive. Of the parents who reported a need for care coordination ( n  = 1049), only 14% of parents reported usually getting the help they needed. More educated, English‐speaking, non‐Hispanic White mothers of older children supported by private insurance were more likely to report never getting as much help coordinating care as desired. Coordination with education services are especially important for children with ASD, yet 27% of parents reported dissatisfaction with PCPs' communication with schools or early intervention. Conclusion: Although parents report a high level of access to PCPs and places for care as well as receiving most core components of the medical home, care coordination activities are lacking for children with ASD. More resourced families are particularly likely to report unmet needs.